Gallstone ileus displaying the typical Rigler triad and an occult second ectopic stone: A case report. Issue 45 (November 2017) - Wang, Li; Dong, Ping; Zhang, Yi; Tian, Bole
Abstract: Rationale: Gallstone ileus is a rare complication of cholecystolithiasis. It has a female predominance and can result in high mortality rates. Patient concerns: A 71-year-old woman complaining of recurrent vomiting and vague epigastralgia for > 2 weeks presented to our department. Diagnosis: Based on her physical examination, laboratory test results and radiographic findings (the typical Rigler's triad), she was diagnosed with gallstone ileus caused by multiple ectopic stones. Interventions: After correction of electrolyte imbalances through parenteral nutrition and fluid management, the patient's condition improved and she underwent enterolithotomy. A 5.3-cm stone located 40 cm from the ligament of Treitz was extracted, and a second ectopic stone, not detected on any imaging modality, was found during laparotomy. Given her comorbidities and overall poor condition, cholecystectomy and fistula repair were not performed. Outcomes: The patient gradually recovered postoperatively. Lessons: Clinical symptoms including epigastralgia with nausea and vomiting, and abdominal CT findings of Rigler's triad (ectopic gallstone, bowel obstruction, and pneumobilia) may lead to early diagnosis of gallstone ileus and enterolithotomy may be the preferred treatment for this condition in the elderly. Laparotomy should involve a systematic and meticulous search for the presence of additional ectopic enteric stones.